Use of calcium chloride in postharvest treatment of Alstroemeria cut flowers - Galati, V. C. [UNESP]; Marques, K. M. [UNESP]; Muniz, A. C.C. [UNESP]; Silva, J. P. [UNESP]; Guimarães, J. E.R. [UNESP]; Mattiuz, C. F.M.; Mattiuz, B. H. [UNESP] (International Society for Horticultural Science (ISHS), 2015)
Cut flowers require the use of technologies to improve postharvest quality and increase floral longevity. The application of calcium in maintenance solutions is used to extend the postharvest preservation. The aim of this study was to investigate the effect of calcium chloride solutions on the postharvest maintenance of Alstroemeria inflorescences. Alstroemeria stems (70 cm) were placed into one-liter Erlenmeyer flasks containing 500 mL of calcium chloride solutions at concentrations of 0, 10, 25, 50 and 100 mmol of calcium L-1, using 3 replications with 3 stems each. Evaluations were performed every three days (0, 3, 6, 9 and 12 days). The flower stems were stored at room temperature (22±1°C and 85±3% RH). The following parameters were assessed: calcium content, fresh weight loss, relative water content, respiration rate, pigments, soluble and reducing carbohydrates, and polyphenoloxidase and peroxidase activity. It was found that the use of 50 mmol of calcium L-1 in the preservation solution prolonged Alstroemeria flower vase life, however, leafyellowing was not delayed.
Keywords: Alstroemeriasp.; Calcium; Longevity; Maintenance solution; Pigments